Ultrasonografie komplikací dialyzacních cévních zkratů: první zkusenosti - Malík, J; Slavíková, M (Casopis lekaru ceskych, 2003)
BACKGROUND: Vascular access complications represent leading morbidity of hemodialyzed patients. Duplex Doppler ultrasonography is used rarely in the diagnosis of vascular access complications, despite its simplicity and widespread availability. Our first experience with this method is described, namely the most frequent indications, findings and the access blood flow correlation. METHODS AND RESULTS: 356 examinations of both natural and polytetrafluoroethylene (PTFE) accesses at 193 patients were performed. The 7.5 MHz linear array ultrasound transducer of Hewlett-Packard SONOS 2000 device was used. Both arterial and venous parts of fistulas were examined in all cases. Screening examinations represented the most frequent indication, the hemodynamically significant stenosis the most frequent finding. Only 12.5% of PTFE-shunts and 25.8% of natural fistulas were described as normal. Mean blood flow through antebrachial and brachial accesses was 575 and 1070 ml/min, respectively. CONCLUSIONS: Prevalence of vascular access complications (especially that of stenoses) is high. Wider use of this method could bring significantly improved care for the dialysed patients.
Keywords: mužské pohlaví; zaváděcí katétry; Regional Blood Flow; Male; Catheters, Indwelling; Arteriovenous Shunt, Surgical; Humans; Female; cévy - implantace protéz; regionální krevní průtok; okluze cévního štěpu; lidé; ženské pohlaví; Graft Occlusion, Vascular; Ultrasonography, Doppler; dialýza ledvin; ultrasonografie dopplerovská; Arm; paže; Renal Dialysis; arteriovenózní zkrat; Blood Vessel Prosthesis Implantation